Effect of Chloride Ion on the Behaviour of Electrolytic Capacitor - Kr. Garg, Pradeep; Agarwal, A. (Asian Journal of Chemistry, 2010)
Aluminum electrolytic capacitors up to 100 working volt, contaminated intentionally with chloride ions, thtough the electrolytic solution were studied. This systematic comparative study was undertaken on the adverse effects of chloride ions on these capacitors, impregnated with 0.4, 0.5, 0.8, 1, 2, 5, 10, 20, 50, 100, 200, 500, 1000 ppm chloride contaminated electrolyte along with uncontaminated electrolyte. The life test of the capacitors was carried out at 85°C up to 2000 h. For these low voltage capacitors the detrimental effect is negligible up to 50 ppm and no remarkable change is observed compared to the uncontaminated electrolyte. Higher chloride concentration has destructive effect in its life test, even in the manufacturing process due to severe anode corrosion, observed thtough photomicrograph. All supporting electrical parameters including ESR of these capacitors have been done extensively in the present article.